Economic Justice in an Unfair World : Toward a Level Playing Field. - Kapstein, Ethan B. (Princeton University Press, 2010)
Recent years have seen a growing number of activists, scholars, and even policymakers claiming that the global economy is unfair and unjust, particularly to developing countries and the poor within them. But what would a fair or just global economy look like? Economic Justice in an Unfair World seeks to answer that question by presenting a bold and provocative argument that emphasizes economic relations among states. The book provides a market-oriented focus, arguing that a just international economy would be one that is inclusive, participatory, and welfare-enhancing for all states. Rejecting.